2013
DOI: 10.1038/ncomms3458
|View full text |Cite|
|
Sign up to set email alerts
|

Larger mammals have longer faces because of size-related constraints on skull form

Abstract: Facial length is one of the best known examples of heterochrony. Changes in the timing of facial growth have been invoked as a mechanism for the origin of our short human face from our long-faced extinct relatives. Such heterochronic changes arguably permit great evolutionary flexibility, allowing the mammalian face to be remodelled simply by modifying postnatal growth. Here we present new data that show that this mechanism is significantly constrained by adult size. Small mammals are more brachycephalic (shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
262
2
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 190 publications
(293 citation statements)
references
References 40 publications
25
262
2
4
Order By: Relevance
“…The trend for the face to elongate with allometry has also been noted in mammals (17) and is postulated to be related to heterochrony, an important factor in the evolution of birds from dinosaurs (46) and a demonstrated mode of generating diversity of beak forms in Darwin's finches (6,9). In mammals, it has been shown that integration constrains evolution along paths of least evolutionary resistance, meaning that heterochronic or allometric changes offer a simple mechanism by which evolution can act to produce high disparity (47,48).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The trend for the face to elongate with allometry has also been noted in mammals (17) and is postulated to be related to heterochrony, an important factor in the evolution of birds from dinosaurs (46) and a demonstrated mode of generating diversity of beak forms in Darwin's finches (6,9). In mammals, it has been shown that integration constrains evolution along paths of least evolutionary resistance, meaning that heterochronic or allometric changes offer a simple mechanism by which evolution can act to produce high disparity (47,48).…”
Section: Discussionmentioning
confidence: 97%
“…Larger animals generally have access to larger prey due to their increased gape and greater absolute muscular power, and size is further related to morphology via allometry, the tendency of traits to vary with size throughout a morphological structure. Allometry has been demonstrated to be a key contributing factor to craniofacial form across a range of mammalian (17,18) and avian (15,19) clades, and evolvability of body size is proposed to be a major evolutionary pathway in the avian stem (20).…”
mentioning
confidence: 99%
“…A focus on craniofacial variation showed that closely related species of mammals often present a common trend, so that smallest species tend to be short-faced and largest ones have proportionally longer faces (Cardini & Polly 2013;Cardini et al 2015a). So far, this has been shown in four lineages of placentals (African antelopes, squirrels and fruit bats, and also mongooses -Cardini & Polly 2013), belonging to different orders, as well as in kangaroos (Cardini et al 2015a).…”
Section: Valkenburgh 2009)mentioning
confidence: 99%
“…Indeed, allometric directions of molar shape changes were not congruent between intra--and inter--population levels, were not parallel to Pmax, and did not contribute significantly to any of the evolutionary shape changes documented here. This undermines the role of allometry as a significant evolutionary force in traits such as murine molars, although allometric constraints may be of prime importance for other traits such as skull (e.g., Cardini and Polly 2013).…”
Section: Limited Role Of Allometry In Molar Shape Evolutionmentioning
confidence: 99%